2017
DOI: 10.2298/pac1703213s
|View full text |Cite
|
Sign up to set email alerts
|

Performances of spin coated silver doped ZnO photoanode based dye sensitized solar cell

Abstract: Dye sensitized solar cells (DSSCs) were fabricated using silver doped ZnO films deposited on ITO glass by spin coating method. The crystalline nature of ZnO films was analysed with XRD and SEM technique was used for morphological studies. The XRD pattern confirmed the presence of single phase hexagonal wurtzite ZnO structure, without the presence of secondary phase. The crystallite size of ZnO decreased from 31 nm to 25 nm with increase in doping to 1.5 mol% of silver. The UV-visible transmission of the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Although efficiency values are low the change in efficiency rate is remarkable when the doping concentration changes. The results of similar type of study in literature, reported that 0.5% Ag-doped ZnO showed the highest efficiency [45].…”
Section: 42photovoltaic Performances Of Dsscs Fabricated Using N719 Dyesupporting
confidence: 68%
“…Although efficiency values are low the change in efficiency rate is remarkable when the doping concentration changes. The results of similar type of study in literature, reported that 0.5% Ag-doped ZnO showed the highest efficiency [45].…”
Section: 42photovoltaic Performances Of Dsscs Fabricated Using N719 Dyesupporting
confidence: 68%
“…It was thus evident that silver ions were deposited by simple soaking in an aqueous AgNO 3 solution on the surface of 8 h-grown ZnO nanorods. It was reported that an improved PCE was achieved when Ag-incorporated ZnO was applied to DSCs [15][16][17][18][19][20]. In those reports, Ag was used in the form of nanoparticle (metal) or as a dopant.…”
Section: Deposition Of Silver Ions On the Zno Nanorod Surfacementioning
confidence: 99%
“…This indicates that metal ions can be adsorbed on the surface of the ZnO particles. DSCs with Ag-decorated ZnO, Ag/ZnO composite or Ag-doped ZnO have been reported [15][16][17][18][19][20], and the Ag incorporation on ZnO layers resulted in an enhancement in PCEs of ZnO-based solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al scrutinized the Ag doped ZnO films as photoanodes with different amount of Ag doping. DSSC with 0.5% Ag doped ZnO film got higher power conversion efficiency of 0.44% 71 . The change in efficiency of DSSC by the doping of photoanode material with different metal atoms has been compared in Table 3.…”
Section: Revamping Of Photoanodementioning
confidence: 99%